2021
DOI: 10.1186/s40798-021-00300-2
|View full text |Cite
|
Sign up to set email alerts
|

Darwinian Selection Discriminates Young Athletes: the Relative Age Effect in Relation to Sporting Performance

Abstract: Background The relative age effect (RAE) is a worldwide phenomenon, allowing sport participation and elite selection to be based on birthdate distribution. Negative consequences include both a narrow, non-optimal elite selection and negative health effects on entire populations. This study investigated the RAE and athletic performance in multiple individual sports in Sweden. Methods Birthdates of athletes born between the years 1922 and 2015 were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Therefore, it is important that organisational structures in cricket attempt to create the most appropriate settings for every young player in order for them to achieve their full potential [ 14 ]. Moreover, Jakobsson and colleagues [ 40 ] suggest another possible issue of selecting based on (bi)annual-age grouping is the violation of the guiding principles by the United Nations Convention on the Rights of the Child (CRC) [ 41 ], which was ratified by the UK in 1991 and is referred to in the UK courts in relation to the Human Rights Act 1998 [ 42 ]. Here, Article 3 in the CRC states how all decisions regarding a child should be made in the best interest of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important that organisational structures in cricket attempt to create the most appropriate settings for every young player in order for them to achieve their full potential [ 14 ]. Moreover, Jakobsson and colleagues [ 40 ] suggest another possible issue of selecting based on (bi)annual-age grouping is the violation of the guiding principles by the United Nations Convention on the Rights of the Child (CRC) [ 41 ], which was ratified by the UK in 1991 and is referred to in the UK courts in relation to the Human Rights Act 1998 [ 42 ]. Here, Article 3 in the CRC states how all decisions regarding a child should be made in the best interest of the child.…”
Section: Discussionmentioning
confidence: 99%
“…At this age, it is possible that chronologically older children have both physical and cognitive advantages. In older age group athletes (15 to 18 years old) in these sports, it is widely reported that the RAE is most significant in elite male athletes [ 1 , 16 ]. The prevalence of the RAE in elite adolescent athletes in these sports may be due to chronologically older peers that are more likely to reach puberty earlier and, therefore, acquire advantages in strength, speed, endurance, and bone strength due to the influence of testosterone [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it is a theory that if a grade is composed of people born from January to December, students born in January will inevitable have better physical, cognitive, and mental development than students born in December (Minsoo, Jiwun, Hyo-Jun, 2021;Sedano, Vaeyens, Redondo, 2015). Today, RAE is a well-known and worldwide phenomenon, influencing the acquisition of young athletes for future elite performance (Jakobsson et al, 2021;Musch, Grondin, 2001), but children with elite-level ambition and potential, born late in the season, have an unjustified lower chance of sport participation past puberty (Jakobsson et al 2021;Baxter-Jones, Helms, 1994). Processes of initiation, identification, and selection are very important but the hazardous procedures, if not made correctly, can lead to talent dispersal.…”
Section: Introductionmentioning
confidence: 99%